Competency-Based Education: Developing an Advanced Competency Framework for Indonesian Pharmacists - Meilianti, Sherly; Smith, Felicity; Bader, Lina; Himawan, Roy; Bates, Ian (Frontiers in Medicine, 2021)
Introduction: Pharmacists need to be adaptable, flexible, and capable of advancing their practice to adapt to rapidly changing population health needs. We describe an educational approach to pharmacy workforce transformation in Indonesia through an advanced practice competency framework development using an “adopt and adapt” methodology. Methods: The competency framework development process comprised a translation phase, an adopt and adapt phase, validation through a nationwide mapping survey, and a completion phase through leadership consensus panels. We conducted a forward-backwards translation of a previously validated Advanced to Consultancy Level Framework (ACLF) to yield the Indonesian Advanced Development Framework (IADF) draft. The subsequent adoption and adaptation process was conducted through a series of consensus panels. We validated the IADF through a nationwide workforce survey. The final phase included leadership consensus panels with the professional leadership body in Indonesia. We analyzed the qualitative data thematically and the quantitative data using a Multiple Correspondence Analysis (MCA) technique. Results: We identified conceptual challenges in adopting and adapting the existing ACLF, which were addressed by providing a national glossary and concrete examples. A total of 6,212 pharmacists participated in the national workforce survey, of which 43% had <2 years of post-license (post-registration) experience. The MCA results showed that practitioner self-assessment to the IADF could discriminate their career development stages. The results also indicated a four-stage career model (including early years career training). Embedding this model in a structured national training program will enhance the professional workforce development through a more structured career journey. Conclusions: We describe the first validation of an advanced competency development framework for the pharmacy workforce in a non-Anglophone country, showing the possibility of transnational applicability of this framework. We argue that this methodology can be used in Low and Middle-income countries (LMICs) for the more rapid advancement of pharmaceutical care practice.